On the Role of Platelet FcγRIIa Phenotype in Heparin-Induced Thrombocytopenia - Brandt, John T; Isenhart, Craig E; Osborne, Jeanne M; Ahmed, Alaa; Anderson, Clark L (Thrombosis and Haemostasis, 1995)
Heparin induced thrombocytopenia (HIT) is characterized by the formation of antibodies that activate normal donor platelets in vitro in the presence of heparin. We asked whether the commonly observed donor-specific variation in the platelet aggregation response to HIT antibodies is influenced by the density of FcγRII on platelets or by the Arg/His 131 allelic polymorphism of platelet FcγRII. We found that platelets with the His/Hisl31 FcγRII phenotype were unresponsive to HIT antibody (0/9) whereas platelets with the Arg/Argl31 phenotype responded well (7/9). His/Hisl31 platelets were largely unresponsive also to a murine IgG1 antiplatelet monoclonal antibody (UR1) known to activate platelets by FcγRII clustering. We then determined the frequency distribution of FcγRIIa Arg/His 131 phenotypes on a series of 200 patients evaluated for HIT and 100 non-thrombocytopenic hospitalized patients. The frequency of the His/Hisl31 phenotype was significantly increased (34.4%) in the 96 thrombocytopenic patients with HIT antibody compared to the 104 thrombocytopenic patients without HIT antibody and the 100 non-thrombocytopenic patients (∼19%). Thus, the FcγRII phenotype regulates the in vitro activation response of normal platelets to HIT antibody and is a risk factor for the thrombocytopenia of HIT